Multi-body power analysis of kicking motion based on a double pendulum - Ozaki, H.; Ohta, K.; Jinji, T. (Procedia Engineering, 2012)
To kick a ball with the maximum velocity, the linear velocity of the kicking foot upon impact must be at the maximum. The dynamical mechanism of the kicking motion must be clarified to better understand the mechanism to produce the maximum velocity of the kicking foot. Therefore, the aim of this study was to clarify the mechanism that produces the maximum foot velocity using mathematical analysis based on a three-dimensional double pendulum model with a moving pivot. We investigated how the non-muscular forces of three components (i.e. centrifugal, Coriolis and gravity) generate, absorb, and transfer energy in order to produce the maximum swing velocity of the leg.